How Do People Cope During the COVID-19 Pandemic and Stay Well? A Salutogenic Longitudinal Study in Israel - Mana, Adi; Catz, Or; Mana, Yossi; Neuman, Moran; Benheim, Sharon; Sagy, Shifra (Frontiers in Psychology, 2021)
Employing the salutogenic approach, this longitudinal study explored the effects of coping with the COVID-19 pandemic in Israel, as it evolved from an acute to a chronic stress situation, during the first year. We examined the role of the individual (sense of coherence), social (perceived social support), and national (sense of national coherence) coping resources, as well as situational and demographic factors, in predicting mental health and anxiety. Data were collected in five phases between March 2020 and February 2021 via a repeated panel sample and included 198 Jewish Israelis (52% males) age 18-64 (M=43.5). The results confirmed the expected pattern of moving from acute to chronic stressful situations: levels of general anxiety were higher in the first phase of the pandemic outbreak as compared to the other phases. Levels of social and national coping resources significantly decreased over time. However, as expected, the salutogenic resource of the individual sense of coherence remained stable and was also found as the main predictor of both anxiety and mental health in the 5 phases of the study. Beyond the explanatory factor of SOC, mental health was better explained by the social and national coping resources, while anxiety was explained by situational factors (level of financial risk and gender). The discussion delineates the longitudinal effects of individual, social, and national coping resources on mental health and anxiety during the dynamic process of the long period of one year of the pandemic, evolving from acute to chronic phases of the complicated health, economic, social, and political crisis